1996
DOI: 10.1111/1540-5885.1320089
|View full text |Cite
|
Sign up to set email alerts
|

Turning New Product Development into a Continuous Learning Process

Abstract: Product developers understand the difficulties of trying to hit a moving target from atop a runaway train. Competitors come and go, technological change occurs at an ever‐increasing rate, customer wants and needs are constantly shifting, and a product's life cycle may be shorter than its development time. We can't meet these challenges with a methodical, step‐by‐step approach to product development. In such a fast‐paced environment, product development must be transformed into a continuous, iterative, learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(17 citation statements)
references
References 36 publications
0
15
0
2
Order By: Relevance
“…Çeşitli araştırmalar NPD takımlarında "öğrenme" kavramını doğrudan veya dolaylı olarak etkileyen faktörleri ele almaktadır (Adams ve diğerleri, 1998, Sarin ve McDermott, 2003, Lynn ve diğerleri, 2000, Lynn ve diğerleri, 2003, Hughes ve Chafin, 1996, Enkel ve diğerleri, 2005. Brooks (1994, s.215)'a göre takım öğrenmesi; sorunları ortaya koyma, bilgi ve fikirlerin paylaşılması, yeni elde edilen bilgilerin birleştirilmesi, dışarıdan veri toplanması ve yeni bilgilerin yaygınlaştırılması süreçlerini içermektedir.…”
Section: Introductionunclassified
“…Çeşitli araştırmalar NPD takımlarında "öğrenme" kavramını doğrudan veya dolaylı olarak etkileyen faktörleri ele almaktadır (Adams ve diğerleri, 1998, Sarin ve McDermott, 2003, Lynn ve diğerleri, 2000, Lynn ve diğerleri, 2003, Hughes ve Chafin, 1996, Enkel ve diğerleri, 2005. Brooks (1994, s.215)'a göre takım öğrenmesi; sorunları ortaya koyma, bilgi ve fikirlerin paylaşılması, yeni elde edilen bilgilerin birleştirilmesi, dışarıdan veri toplanması ve yeni bilgilerin yaygınlaştırılması süreçlerini içermektedir.…”
Section: Introductionunclassified
“…Phase-Review-Process (Hughes, Chafin, 1996) As shown in figure 7 the innovation process is separated in phases. A Management…”
Section: Social Innovationmentioning
confidence: 99%
“…Cycle" which was originally used in an organization which before had used the StageGate-Process (Hughes, Chafin, 1996).…”
Section: Social Innovationmentioning
confidence: 99%
See 2 more Smart Citations